Suppression of the Shastry-Sutherland phase in Ce2Pd2Sn at a field-induced critical point - Sereni, J.G.; Gómez Berisso, M.; Schmerber, G.; Kappler, J.P.; Sereni, Julián (American Physical Society, 2010)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina